If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(p + 3) = -2(6p + -3) Reorder the terms: 2(3 + p) = -2(6p + -3) (3 * 2 + p * 2) = -2(6p + -3) (6 + 2p) = -2(6p + -3) Reorder the terms: 6 + 2p = -2(-3 + 6p) 6 + 2p = (-3 * -2 + 6p * -2) 6 + 2p = (6 + -12p) Add '-6' to each side of the equation. 6 + -6 + 2p = 6 + -6 + -12p Combine like terms: 6 + -6 = 0 0 + 2p = 6 + -6 + -12p 2p = 6 + -6 + -12p Combine like terms: 6 + -6 = 0 2p = 0 + -12p 2p = -12p Solving 2p = -12p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '12p' to each side of the equation. 2p + 12p = -12p + 12p Combine like terms: 2p + 12p = 14p 14p = -12p + 12p Combine like terms: -12p + 12p = 0 14p = 0 Divide each side by '14'. p = 0 Simplifying p = 0
| 195=-5+8(1+4x) | | 7y-2=8y-32 | | -4x+5y-7z+3x+5z-2y= | | 4-q=-1 | | 5x+6=-3+9 | | -2[x-6]+7=35 | | 5(4y-1)-2=6(3y-4)+3 | | 2[4w-1]=3[4w+2] | | 12x-10=130 | | 4(b-8)+8b=12b-69 | | -2w+4=6w-6+2w+12 | | 48-2g=34 | | 7n^2+31n+12=0 | | -7v+10v=-3(1-3v)-(5v-4) | | -13+3n=4n-7(n-5) | | 8m+21+1m=35 | | 27x-5=-15x-113 | | 2(5c+2)-2=3(2c+3) | | 5k^2-21k-54=0 | | 8x-3=3(3x-4) | | 10x+3=-83 | | -7(-11-11n)=-6n+3(11n+9) | | 2(3p-7)-15= | | -7/8x+9=4/5x-17 | | |x-1/4|=2 | | -5=x+17 | | 12y-32-2y=4y-32-3 | | 5r^2+46r+9=0 | | 2.5(a+7)=1.5(a-.5) | | 2/5m=7/8 | | n-39+3(3n+3)= | | 7p+3=3p+13 |